The Influence of Teamwork and Competence on Performance in Hospital Services - Puspitasari, Natalia Desi; Qomariah, Nurul; Martini, Ni Nyoman Putu Martini (Budapest International Research and Critics University, 2024)
Every organization has an obligation to improve performance, both individual employee performance and organizational performance. This performance improvement is important considering that currently competition occurs in all sectors. This research aims to determine the impact of teamwork and competence on performance at RSU dr. Koesnadi Bondowoso. This research uses 2 (two) types of variables, namely the independent variable (cooperation and competence) and the dependent variable (employee performance). The research population was all employees at RSU dr. Koesnadi Bondowoso, numbering 374. Meanwhile, the sample was 100 using the Slovin method. Descriptive analysis is used, namely knowing the description of respondents and variables. Validity test analysis and reliability test are used to test the measuring instruments used. Hypothesis testing analysis to test the research hypothesis developed in the research. The results of the analysis show that competency has a positive impact on employee performance. Meanwhile, teamwork has an impact on employee performance at RSU dr. Koesnadi Bondowoso.